PERAN ORANG TUA DALAM PENYESUAIAN DIRI ANAK TUNAGRAHITA DI SEKOLAH LUAR BIASA PGRI GENTENG BANYUWANGI - Eka Ramiati; Yuli Tri Andini (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
Being a parent is a very meaningful gift to every couple, especially with the presence of a child who is the epitome of love for both of her parents. If a child is born in a state of mental disability or a tunagrahita, then the parent will begin to think about how they should raise the child who is mentally disabled. The fact that is happening in the community about the parenting of disabled is the number of parents who let even hide the children of disabled because of shame, but there are also parents who give good parenting to them. The purpose of this study is to explain and give an overview of the form of self-adjustment and the cause of the children's causes, the factors that cause self-adjustment in children, the factors that influence self-adjustment Children and to know how the role of parents in assisting the self-adjustment of the child is a disabled. The study used a qualitative approach in the form of case studies. The characteristics of the subject in this study were 15-year-old disabled children and male genders, while the characteristics of respondents in this study were married couples who had a 30-50-year-old child of disabled . Based on the results of the research known that the form of self-adjustment of children such as those who want to be independent, have the same desire with normal people, social interaction, have self control, and confident. The cause of child disabled is due to high fever pain (convulsions) and the economic difficulties of the subject family, so that their child is too late to get treatment that eventually leads to disabled. Factors that are the cause of self-adjustment in the child are physical and psychological factors and environmental factors, namely the attention of the environment, such as family members and neighbors around the place of residence. In an effort to adjust itself, the child needs a good role of parents, which provides proper support and parenting. Parenting roles include material support, attention support, parental acceptance, advice and parenting.